1994
DOI: 10.1180/claymin.1994.029.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Thermogravimetric, Infrared and Mass Spectroscopic Analysis of the Desorption of Tetrahydropyran, Tetrahydrofuran and 1,4-Dioxan from Montmorillonite

Abstract: A B ST R A C T : The desorption of tetrahydropyran (THP), tetrahydrofuran (THF) and 1,4-dioxan (DIOX) from Na +-, Ca 2+-, AI 3+-and Cr3+-exchanged montmorillonite has been studied using variable temperature infrared spectroscopy and thermogravimetric analysis. The derivative thermograms for the desorption of each cyclic ether exhibited three maxima but there was little uniformity in the temperatures at which these maxima occurred. Nonetheless, the desorption of both THP and THF occurred at lower temperatures i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
(13 reference statements)
1
13
1
Order By: Relevance
“…Unfortunately, a quantitative explanation of these phenomena was not given. In some systems, a competition between basic dye and cationic surfactant occurred during the sorption [40]. Gupta et al [41] have found a negligible effect of an anionic surfactant (Manoxol B) on the sorption of triphenylmethane basic dye (basic red 9) on carbon slurry or blast furnace slag.…”
Section: Equilibrium Measurementsmentioning
confidence: 98%
“…Unfortunately, a quantitative explanation of these phenomena was not given. In some systems, a competition between basic dye and cationic surfactant occurred during the sorption [40]. Gupta et al [41] have found a negligible effect of an anionic surfactant (Manoxol B) on the sorption of triphenylmethane basic dye (basic red 9) on carbon slurry or blast furnace slag.…”
Section: Equilibrium Measurementsmentioning
confidence: 98%
“…Besides attractive electrostatic forces, the dye adsorption is accelerated by molecular aggregation of the organic cations. Consequently, dyes are adsorbed in the form of molecular assemblies and almost irreversibly [4]. The aggregation significantly affects the optical properties of adsorbed chromophores [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The cations are adsorbed via ion exchange, frequently accompanied by agglomeration, where micelles consisting of three or more cations at the clay surface orient via π−π interaction on both sides of the molecular plane with two neighboring cations. A partial protonation of MB cations may also take place at clay surfaces in a manner similar to that in very acidic solutions. , Visible spectra of MB−clay suspensions contain several bands assigned to the absorption of monomers, dimers, agglomerates (near 575 nm), and protonated MBH 2+ cations (at about 765 nm) …”
Section: Introductionmentioning
confidence: 99%
“…(1) More than 75% of the dye may agglomerate at greater (MB amount/CEC; CEC = cation exchange capacity) loadings. Large amounts of agglomerates were found also in fresh suspensions. In dilute suspensions of Na−smectites, individual clay layers are present and both the edges and the basal surface sites are accessible for MB . An absence of agglomerates of MB cations at the basal surfaces would mean that adsorbed MB cations are predominantly located at the clay particle edges, which is not probable.…”
Section: Introductionmentioning
confidence: 99%